The deep historical roots of macroeconomic volatility - Sam Hak Kan Tang; Charles Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2016)
We present cross-country evidence that a country's macroeconomic volatility, measured either by the standard deviation of output growth or the occurrence of trend-growth breaks, is significantly affected by the country's historical variables. In particular, countries with longer histories of state-level political institutions experience less macroeconomic volatility in postwar periods. Robustness checks reveal that the effect of this historical variable on volatility remains significant and substantial after controlling for a host of structural variables investigated in previous studies. We also find that the state history variable is more important in countries with a higher level of macroeconomic volatility.
Keywords: O10; O33; O43; 330; Macroeconomic volatility; history of State-level institution; History of agriculture; Technology adoption; Political stability